Joint surgery in the Utrecht Rheumatoid Arthritis Cohort: the effect of treatment strategy - Verstappen, S M M (BMJ Group, 2006)
OBJECTIVE: To investigate the prevalence and prognostic factors of joint surgery in a large cohort of patients with rheumatoid arthritis, whose treatment, clinical and radiographic data have been assessed at predefined points in time since disease onset. METHODS: Data on surgical interventions were retrospectively obtained from 482 patients with rheumatoid arthritis whose follow‐up data for at least 2 years were available, including treatment and response to treatment during the first 2 years. Survival time until the first surgical intervention and until the first major surgical intervention was determined for the total study population by Kaplan–Meier survival curves. Three separate Cox regression analyses were carried out to determine which variables measured at baseline, during the first year and during the first 2 years were predictors for joint surgery. RESULTS: 27% of the patients underwent surgical interventions. Mean survival time until the first surgical intervention was 10.4 years. The percentage of patients with a surgical intervention was 10% lower in the group with response to treatment when compared with the non‐response group. Next to a delayed start with disease‐modifying antirheumatic drugs, fast radiographic progression during the first year and first 2 years was a predictor of joint surgery in the multivariate regression analyses. CONCLUSION: Treatment with disease‐modifying antirheumatic drugs immediately after diagnosis results in less joint surgery when compared with a delayed start. Furthermore, joint surgery is carried out more often in patients who do not respond to treatment.